Radiological Studies in Very Low Birth Weight and Extremely Low Birth Weight Neonates: 'ALARA' Revisited. (31st December 2019) - Jeetoo, Surjit Damon; Smith, Johan; Pitcher, Richard Denys
Abstract: Background: Very low birth weight (VLBW) and extremely low birth weight (ELBW) neonates are particularly susceptible to the adverse effects of ionizing radiation. There are limited data on radiographic practice among this population in resource-limited environments. Aim: To estimate cumulative effective dose (ED) from diagnostic imaging in VLBW (1000–1500 g) and ELBW (<1000 g) neonates in a resource-limited setting. Method: A retrospective analysis of all diagnostic imaging examinations performed on ELBW and VLBW neonates born in a large South African public-sector tertiary-level hospital from January through June 2015. Data were stratified by birth weight and imaging examination. The ED was estimated according to the method of Puch-Kapst. Non-parametric t -tests compared the number of radiographs and ED in VLBW and ELBW neonates, at 5% significance. Results: Three hundred and ninety-three neonates with median birth weight 1130 (IQR: 930–1340) g were included; 265 (67%) were VLBW and 128 (33%) ELBW; 48 (12%) died at a median of 7 (IQR: 2–17) days. A median of 2 (IQR: 1–5) radiographs were performed per neonate, with median ED 28.8 (IQR: 14.4–90.8) μSv. The median radiographic exposures for VLBW and ELBW neonates were 1 (IQR: 1–4) and 4 (IQR: 2–9), respectively, ( p  < 0.0001) with median ED 14.4 (IQR: 14.4–70.4) μSv and 71.2 (IQR: 28.8–169.3) μSv, respectively, ( p  < 0.0001). Radiographic exposure for VLBW neonates was lower than previously documented for this population. Conclusion: Neonatal radiographic practice in resource-limited settings has the potential to contribute to the discourse on international best practice.